Ziemiaństwo polskie wobec dyskusji o zasadzie przymusowego wywłaszczenia ziemi w I Dumie Państwowej. Zjazd agrarny w Warszawie 27-30 listopada 1906 r. i jego znaczenie - Jurkowski, Roman (Przegląd Wschodnioeuropejski, 2023)
The article concerns the attitude of the Polish landed gentry to the principle of compulsory expropriation of land, which was accepted in the 1st State Duma by the Polish Circle of the Kingdom of Poland. The Polish conservatives grouped in the Party of Real Politics were decisive opponents of the forced expropriation of private land. In November 1906, they organized a special congress on the agrarian issue in Warsaw in order to receive an assurance from the National-Democratic Party that the party would not support any projects of forced expropriation of lands in the future Duma. At the agrarian congress, the participants discussed ways to restore agriculture in Russia and the Kingdom of Poland, as well as the future cooperation of both parties in the upcoming elections to the Second State Duma (1907).